Green Finance, Innovation and the Energy-Environment-Climate Nexus - Zhang, Kai Quan; Chen, Hsing Hung; Tang, Li Zhi; Qiao, Sen (Frontiers in Environmental Science, 2022)
After the Paris Climate Conference (COP21), carbon neutrality and environmental sustainability have become the consensus of many countries. Technological innovation and green finance are the essential factors that can help to realize clean energy transition, carbon emission reduction and climate change mitigation. To investigate the pathways for sustainable development, this study includes innovation and green finance into simultaneous equations models within energy-environment-climate nexus. We examine the dynamic relationships for a sample of 49 countries with green bonds issued for the period 2007-2019. The results confirm that there are bidirectional relationships among renewable energy consumption, environmental pollution and climate change. Innovation can significantly promote renewable energy consumption, reduce CO2 emissions and mitigate climate change. Green finance can effectively alleviate environmental pollution and climate change. Accelerating the development of green finance is the primary motivation for sustainable development. Green finance moderates the relationship between innovation and energy-environment-climate nexus. The positive impact of innovation on renewable energy consumption is enhanced by higher level of green finance. When the development of green finance is high, innovation has a greater negative influence on CO2 emissions, and the impact of innovation on climate change is weakened.